Price disparity in international commodity markets: the case of Malaysian key exports - Baharumshah, Ahmad Zubaidi; Habibullah, Muzafar Shah (Universiti Putra Malaysia, 1994)
According to the law of one price (LOP), the export price of a well defined commodity should be the same in different markets. This paper investigates the empirical validity of this hypothesis using cointegration technique suggested by Engle and Granger (1985) and Johansen (1988). Monthly data on the export prices of rubber, palm oil and timber products were used to analyze the long-run equilibrium relationship. Both the residual based tests and the maximum likelihood procedures produced results that are not supportive of the LOP as a long-run relationship. We conclude that the exchange rate pass-through on the export prices to be incomplete and international markets are not competitive.